2017
DOI: 10.3389/fchem.2016.00048
|View full text |Cite
|
Sign up to set email alerts
|

From Stock Bottle to Vaccine: Elucidating the Particle Size Distributions of Aluminum Adjuvants Using Dynamic Light Scattering

Abstract: The physicochemical properties of aluminum salts are key determinants of their resultant adjuvanticity in vivo when administered as part of a vaccine. While there are links between particle size and the efficacy of the immune response, the limited literature directly characterizing the PSD of aluminum adjuvants has stymied the elucidation of such a relationship for these materials. Hence, this comparative study was undertaken to monitor the PSD of aluminum adjuvants throughout the process of vaccine formulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 47 publications
5
28
0
3
Order By: Relevance
“… 25 , 26 These nanoparticles form loosely connected porous aggregates that vary in size from 1 to about 20 µm depending on the adjuvant, the method used for measurement of particle size, and the experimental conditions. 27 30 Exposure to shear forces and ultrasonication decreased the size of the aggregate adjuvant particles, 28 , 29 whereas suspension of adjuvants in saline increased aggregation and the size of the aggregates. 30 , 31 The ability of the aggregates to dissociate and reaggregate upon mixing contributes to the even distribution of adsorbed antigens in vaccine formulations.…”
Section: Formulation Of Vaccines With Aluminum Adjuvantsmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 , 26 These nanoparticles form loosely connected porous aggregates that vary in size from 1 to about 20 µm depending on the adjuvant, the method used for measurement of particle size, and the experimental conditions. 27 30 Exposure to shear forces and ultrasonication decreased the size of the aggregate adjuvant particles, 28 , 29 whereas suspension of adjuvants in saline increased aggregation and the size of the aggregates. 30 , 31 The ability of the aggregates to dissociate and reaggregate upon mixing contributes to the even distribution of adsorbed antigens in vaccine formulations.…”
Section: Formulation Of Vaccines With Aluminum Adjuvantsmentioning
confidence: 99%
“… 27 30 Exposure to shear forces and ultrasonication decreased the size of the aggregate adjuvant particles, 28 , 29 whereas suspension of adjuvants in saline increased aggregation and the size of the aggregates. 30 , 31 The ability of the aggregates to dissociate and reaggregate upon mixing contributes to the even distribution of adsorbed antigens in vaccine formulations. 32 The primary nanoparticles that make up the aggregates provide a very large surface, estimated at 514 m 2 /g for AH (Rehydragel HPA), when measured by water adsorption using gravimetric infrared spectroscopy.…”
Section: Formulation Of Vaccines With Aluminum Adjuvantsmentioning
confidence: 99%
“…Hydrodynamic analyses of ABA suspensions also have their limitations mainly due to the polydispersity of the preparations themselves; however, such methodologies provide an informative reference PSD under relevant environmental conditions. Our group recently reported that the median particle size of Alhydrogel ® and Adju-Phos ® by dynamic light scattering (DLS) was ca 3 and 7 μm respectively [ 89 ]. The latter was in good agreement with that obtained by Kolade et al using low angle laser light scattering for an equivalent commercial preparation ( ca 6 μm) [ 90 ].…”
Section: The Physicochemical Properties Of Abas and Their Respective mentioning
confidence: 99%
“…The disordered, amorphous state is responsible for the high surface area and high adsorptive capacity of this adjuvant whose plate-like particles have a diameter of approximately 50 nm (11,12). The nanoparticles of this aluminium adjuvant form loosely connected porous aggregates that vary in size from 1 to about 20 μm depending on the adjuvant, the method used for measurement of particle size, and the experimental conditions (13,14). Another commercially available adjuvant is amorphous aluminum hydroxyphosphate sulfate, which contains residual sulfate residues because alum was used instead of aluminum chloride for its synthesis.…”
Section: Table Imentioning
confidence: 99%
“…The size of the aggregate adjuvant particles can be decreased (i.e. during exposure to shear forces and ultrasonication (13) or increased when these particles are suspended in saline solution (14). The morphology of aluminum-containing adjuvants contributes to the uniform distribution of antigen in vaccines (11).…”
Section: Table Imentioning
confidence: 99%